PI3K activation allows immune evasion by promoting an inhibitory myeloid tumor microenvironment - Yashaswi Shrestha; Michael Quigley; Travis Hughes; Robert T Manguso; Natalie B Collins; Rose Al Abosy; Brian C Miller; Kevin Bi; Qihong Zhao; Jeffrey J Ishizuka; Kathleen B Yates; Hans W Pope; et al. (Journal for ImmunoTherapy of Cancer)
Background Oncogenes act in a cell-intrinsic way to promote tumorigenesis. Whether oncogenes also have a cell-extrinsic effect on suppressing the immune response to cancer is less well understood.Methods We use an in vivo expression screen of known cancer-associated somatic mutations in mouse syngeneic tumor models treated with checkpoint blockade to identify oncogenes that promote immune evasion. We then validated candidates from this screen in vivo and analyzed the tumor immune microenvironment of tumors expressing mutant protein to identify mechanisms of immune evasion.Results We found that expression of a catalytically active mutation in phospho-inositol 3 kinase (PI3K), PIK3CA c.3140A>G (H1047R) confers a selective growth advantage to tumors treated with immunotherapy that is reversed by pharmacological PI3K inhibition. PIK3CA H1047R-expression in tumors decreased the number of CD8+ T cells but increased the number of inhibitory myeloid cells following immunotherapy. Inhibition of myeloid infiltration by pharmacological or genetic modulation of Ccl2 in PIK3CA H1047R tumors restored sensitivity to programmed cell death protein 1 (PD-1) checkpoint blockade.Conclusions PI3K activation enables tumor immune evasion by promoting an inhibitory myeloid microenvironment. Activating mutations in PI3K may be useful as a biomarker of poor response to immunotherapy. Our data suggest that some oncogenes promote tumorigenesis by enabling tumor cells to avoid clearance by the immune system. Identification of those mechanisms can advance rational combination strategies to increase the efficacy of immunotherapy.